2015
DOI: 10.1520/gtj20140215
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Soil to Model Thermal Processes: An Energy Pile Example

Abstract: Managing energy resources is fast becoming a crucial issue of the 21st century, with groundbased heat exchange energy structures targeted as a viable means of reducing carbon emissions associated with regulating building temperatures. Limited information exists about the thermo-dynamic interactions of geothermal structures and soil owing to the practical constraints of placing measurement sensors in proximity to foundations; hence, questions remain about their long-term performance and interaction mechanics. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The temperature was kept at 25 °C during the experiments to eliminate its influence on the refractive indices of the pore fluids (Siemens et al 2015;Black and Tatari 2015). The refractive index of the fused quartz particles supplied by the manufacturer equals 1.45.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…The temperature was kept at 25 °C during the experiments to eliminate its influence on the refractive indices of the pore fluids (Siemens et al 2015;Black and Tatari 2015). The refractive index of the fused quartz particles supplied by the manufacturer equals 1.45.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Black and Take (2015) and Black and Tatari (2015) demonstrated that changes in temperature affect the refractive index of transparent soil and consequently reduce its visual acuity. Current state-of-the-art transparent soil tests are conducted at 1 g in temperaturecontrolled laboratories whereby the model temperature and ambient room temperature are carefully controlled and maintained.…”
Section: Test Setup and Proceduresmentioning
confidence: 99%
“…However, the change in the transparency of transparent soil can also be a favorable factor in the test [17,18]. Based on this understanding, the relationship between transparency of transparent soil and temperature was established through experiments, and the temperature field around the energy pile was studied [17]. It was proved that the continuous temperature field around the structure could be obtained based on the change in the transparency of transparent soil.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in transparency caused by temperature, saturation and impurities are considered to be unfavorable factors in the transparent soil test; these factors need to be strictly controlled in the test. However, the change in the transparency of transparent soil can also be a favorable factor in the test [17,18]. Based on this understanding, the relationship between transparency of transparent soil and temperature was established through experiments, and the temperature field around the energy pile was studied [17].…”
Section: Introductionmentioning
confidence: 99%